Lidocaine effects on corneal endothelial cell ultrastructure - Schellini, Silvana Artioli [UNESP]; Creppe, Marcelo Crivellari; Gregorio, Elisa Aparecida; Padovani, Carlos Roberto [UNESP] (Blackwell Publishing, 2007)
The purpose of this study was to determine whether intracameral commercial lidocaine 2% induces alterations on the rabbit corneal endothelium. Forty white rabbits received different substances inside the anterior chamber: group (G)1, no substance; G2 and G3 received lidocaine 2% with preservative in aqueous solution; G4 and G5, lidocaine 2% with preservative in gel solution; G6 and G7, the anesthetic preservative (metilparahydroxybenzoate 0.1%); and G8 and G9, lidocaine 2% without preservative in aqueous solution. The animals from G2, 4, 6 and 8 were sacrificed after 1 h, and from G3, 5, 7 and 9 after 24 h after injection of the substance inside the anterior chamber. The corneas were clinically evaluated and assessed by transmission and scanning electron microscopy. G1, 2, 6, 7, 8 and 9 animals had very similar characteristics in clinical, ultrastructural and morphometric evaluations; the G3 and G4 animals showed discrete edema and one animal in G5 had intense corneal edema. We conclude that lidocaine 2% with preservative induces few ultrastructural alterations in the corneal endothelial cells.
Keywords: corneal endothelial; experimental study; lidocaine; local anesthesia; rabbit; ultrastructure